Modified Electromagnetic Actuator for Active Suspension System - Prajwal V R; Chandrashekar Murthy B N; Yashwanth S D (International Journal of Engineering and Management Research, 2021)
Active suspension is a type of suspension systems which can vary its damping value in order to adjust the spring firmness in accordance with the road conditions. Real Active Suspension incorporates an external actuator which helps in raising or lowering of vehicle chassis independently at each wheel. Generally, the actuators that are used for active suspension are Hydropneumatic, Electro-hydraulic or Electromagnetic actuators. A new concept of two-way electromagnetic actuation with the help of magnetic damping is proposed in this paper, which can extend its arm on both sides to facilitate active suspension mechanism in both humps and potholes. This increases the ride quality while maneuvering not only in humps, but also in dumps. It also describes about the comparison of spring materials, sophisticated design, construction and working principle of newly proposed actuator. Catia V5 software has been used to design and simulate the actuator model, different spring materials are analyzed and their shear stress and deflections are compared.